ANALISIS PENGARUH KEMISKINAN TERHADAP AKSES LAYANAN KESEHATAN DI KABUPATEN MIMIKA - Borgen Extri Arens Lona; Herniagus Tandi Dannari (CV. Adiba Aisha Amira, 2025)
This study aims to determine the eflect of poverty on access to health services in Mimika Regency. The data collection technique used to obtain data in this study is the questionnaire technique and the application used is SPSS version 25. Data analysis in this study uses Chi square analysis. Based on the results of the data analysis carried out in this study, the author concludes that there is an eflect of poverty on access to health services in Mimika Regency. There are four indicators of access to health services that are assessed in the study, namely distance, transportation costs, friendliness and satisfaction which have very significant results on the eflect of poverty on access to health services.